Efficacy of traditional Thai massage as adjunctive therapy in patients with major depressive disorder - Warangkana Chompoopan; Wichai Eungpinichpong; Suwanna Arunpongpaisal; Worawut Chompoopan (Tabriz University of Medical Sciences, 2024)
Background: Major depressive disorder (MDD) is the most common mental ailment. Moreover, it is one of the most incapacitating medical conditions. Although antidepressant medication has traditionally been the mainstay of treatment, adjunctive therapy may provide therapeutic advantages that reduce the severity of depression. Methods: An experiment using randomization and control groups was undertaken. A total of forty-eight individuals diagnosed with severe depressive illness and undergoing antidepressant medication were selected and randomly assigned to either get traditional Thai massage (TTM) treatment, consisting of 90-minute sessions twice a week for eight weeks, or to be part of the control group, which continued with their regular daily activities. The main assessment tools used were the Hamilton Depression Rating Scale (HAM-D), the Clinical Global Impression-Severity (CGI-S), and the Khon Kaen University Depression Inventory 14 (KKU-DI-14). Secondary outcomes, such as blood pressure (BP) and quality of life measured by The EuroQol-5D-5L (EQ-5D-5L), were assessed both before and after the first therapy, as well as at the last session at the 8th week. Results: The TTM group showed a statistically significant decrease in the HAM-D score within the eighth week of therapy compared to the control group (5.14 points, 95% confidence interval=2.92 to 7.37 points, P<0.001). Conclusion: These findings suggest that combining TTM with antidepressant medication may effectively reduce depression scores and improve quality of life scores.